Informatika Implementasi Aplikasi Point Of Sale Berbasis Web Pada Percetakan Amanah Offset Printing - Niasari, Fitri; Julianti, Fitri; Supriyatna; Marlina, Siti; Latif , Abdul (Management of Information System Journal, 2025)
− This study aims to design and develop a web-based sales information system using the Waterfall method at Amanah Offset Printing. The system was built using PHP Native, MySQL, and Laragon to manage sales transactions, raw material purchases, inventory, customer data, and financial reports in an integrated manner. The test results show that the system meets user requirements, improves transaction management efficiency, data accuracy, and simplifies realtime financial reporting.